Home Online Manual
Back: ratgb_lib
Forward: dmodloc_lib
Up: ratgb_lib
Top: Singular Manual
Contents: Table of Contents
Index: Index
About: About this document ratstd
Procedure from library ratgb.lib (see ratgb_lib).

ratstd(I, n [,eng]); I an ideal/module, n an integer, eng an optional integer


compute the Groebner basis of I in the Ore localization of the basering with respect to the subalgebra, generated by first n variables

the variables of basering are organized in two blocks and - the first block of length n contains the elements with respect to which one localizes, - the basering is equipped with the elimination block ordering for the variables in the second block

the output ring C is commutative. The ideal rGBid in C represents the rational form of the output ideal pGBid in the basering. - During the computation, the D-dimension of I and the corresponding dimension as K(x)-vector space of I are computed and printed out. - Setting optional integer eng to 1, slimgb is taken as Groebner engine

In order to see the steps of the computation, set printlevel to >=2

LIB "ratgb.lib";
ring r = (0,c),(x,y,Dx,Dy),(a(0,0,1,1),a(0,0,1,0),dp);
// this ordering is an antiblock ordering, as it must be
def S = Weyl(); setring S;
// the ideal I below annihilates parametric Appel F4 function
// where we set parameters to a=-2, b=-1 and d=0
ideal I =
x*Dx*(x*Dx+c-1) - x*(x*Dx+y*Dy-2)*(x*Dx+y*Dy-1),
y*Dy*(y*Dy-1) - y*(x*Dx+y*Dy-2)*(x*Dx+y*Dy-1);
int is = 2; // hence 1st and 2nd variables, that is x and y
// will become invertible in the localization
def A = ratstd(I,2); // main call
==> the D-dimension is 0
==> the K-dimension is 4
pGBid; // polynomial form of the basis in the localized ring
==> pGBid[1]=2*x*y*Dx*Dy+x*y*Dy^2+y^2*Dy^2-y*Dy^2+(-c-2)*x*Dx-2*y*Dy+2
==> pGBid[2]=x*Dx^2-y*Dy^2+(c)*Dx
==> pGBid[3]=2*x^2*y*Dy^3-4*x*y^2*Dy^3+2*y^3*Dy^3-4*x*y*Dy^3-4*y^2*Dy^3+2*y*D\
setring A; // A is a commutative ring used for presentation
rGBid; // "rational" or "localized" form of the basis
==> rGBid[1]=(2*x*y)*Dx*Dy+(x*y+y^2-y)*Dy^2+(-c*x-2*x)*Dx+(-2*y)*Dy+2
==> rGBid[2]=(x)*Dx^2+(-y)*Dy^2+(c)*Dx
==> rGBid[3]=(2*x^2*y-4*x*y^2-4*x*y+2*y^3-4*y^2+2*y)*Dy^3+(-2*c*x^2+2*c*x)*Dx\
//--- Now, let us compute a K(x,y) basis explicitly
==> // ** rGBid is no standard basis
==> Dy^2,Dy,Dx,1